Acknowledgement - Herodotou, Maria (Études helléniques / Hellenic Studies, 1999)
As guest editor I wish to express my gratitude to the editorial board of Etudes helleniques/Hellenic Studies for devoting this issue to Greeks in Australia and thus recognising the importance of this vital part of the Greek Diaspora. I would also like to thank the contributors to this volume; Dr Despina Michael for the corrections of the texts and the Department of Hellenic Studies, La Trobe University, for all its support.